Dampak Continuity Of Care Yang Diberikan Oleh Mahasiswa Kebidanan Terhadap Kepercayaan Perempuan Terhadap Pelayanan Kesehatan - Fitrayeni, Fitrayeni; Iffah, Uliy; Ridwan, Laila Hijradesy (Afiasi : Jurnal Kesehatan Masyarakat, 2025)
Background: Continuity of Care (CoC) is a midwifery care approach emphasizing continuous and interpersonal relationships between health providers and women throughout pregnancy, childbirth, postpartum, and family planning periods. Objective: This study aimed to analyze the impact of CoC implementation by midwifery students on women’s trust in health services. Methods: The research involved 30 women who received CoC care from students of the Midwifery Professional Program, Faculty of Medicine, Andalas University. Data were collected through observation of CoC implementation and a validated trust questionnaire covering four dimensions: students’ competence, interaction comfort, confidentiality, and readiness to receive care. Results: Statistical analysis using a paired t-test showed a significant increase in women’s trust scores after receiving CoC (mean score increased from 3.2 to 4.4; p < 0.05). Linear regression analysis indicated that the quality of CoC implementation significantly influenced women’s trust levels (R² = 0.52). Conclusion: These findings demonstrate that CoC provided by midwifery students not only enhances the quality of care but also strengthens the trust relationship between women and health providers. The results are expected to contribute to the development of midwifery education curricula emphasizing continuity of care and empathy in clinical practice.